Potential distribution of main malaria vector species in the endemic Colombian Pacific region (2020)
ABSTRACT: Objective To assess the existing fundamental niche, potential distribution and degree of niche overlap for the three main Colombian malaria vectors Anopheles albimanus, Anopheles darlingi and Anopheles nuneztovari in the major malaria endemic Pacific region. Methods We used models based on presence records and Normalised Difference Vegetation Index (NDVI) data, created using the maximum entropy algorithm. Results The three vector species occupied heterogeneous environments, and their NDVI values differed. Anopheles albimanus had the largest niche amplitude and was distributed mainly on coastal areas. Environmentally suitable areas for An. albimanus and An. nuneztovari were the dry forest of inter-Andean Valleys in south-western Colombia, as confirmed for An. albimanus during model validation. There was a slight degree of niche overlap between An. darlingi and An. nuneztovari, and the species co-occurred in humid forests, predominantly in riparian zones of the San Juan and Atrato rivers. Conclusion The information obtained may be used for the implementation of vector control interventions in selected priority areas to reduce malaria risk in this region while optimising resources.